Measuring early childhood development in multiple contexts: the internal factor structure and reliability of the early Human Capability Index in seven low and middle income countries - Sincovich, Alanna (BMC Pediatr, 2019)
BACKGROUND: The fourth year of the Sustainable Development Agenda era calls for countries to continue to invest not only in interventions and policies that will promote global equity and sustainability, but also in the monitoring systems required to track progress against these targets. A more pragmatic solution to measuring children’s early development in low and middle income countries in particular, is required. This study explores the psychometric properties of the early Human Capability Index (eHCI), a population measure of holistic development for children aged 3–5 years, designed with the vision of being flexible and feasible for use in low resource and capacity settings. METHODS: Utilizing data from seven low and middle income countries: Brazil (n = 1810), China (n = 11,421), Kiribati (n = 8339), Lao People’s Democratic Republic (n = 7493), Samoa (n = 12,191), Tonga (n = 6214), and Tuvalu (n = 549), analyses explored the internal factor structure and reliability of scores produced by the tool within each country. RESULTS: Confirmatory factor analyses and internal consistency coefficients demonstrated that after local adaptation, translation, and different implementation methods across countries, the eHCI maintained the same factor structure of nine theoretically-based developmental domains: Physical Health, Verbal Communication, Cultural Knowledge, Social and Emotional Skills, Perseverance, Approaches to Learning, Numeracy, Reading, and Writing. CONCLUSIONS: Findings support the aims of the eHCI in being adaptable and applicable for use within a range of low and middle income countries to facilitate measurement and monitoring of children’s early development, as is required for the tracking of progress towards the Sustainable Development Agenda.